Impact of International Sports Event on Local Businesses: Insight from the Stallholders and Official Partners of the 2018 Asian Games - Uka Wikarya; Amalia Adininggar Widyasanti; Mohamad Dian Revindo; Chairina Hanum Siregar; Calista Endrina Dewi (Universitas Negeri Semarang, 2022)
International mega sports events commanding massive public spending are expected to stimulate the economic development of the host country. This study aims to examine the impact of the 2018 Asian Games Jakarta-Palembang on local businesses, captured through the perspectives of micro, small and medium-sized enterprises (MSMEs) and official partners of the event. Primary data were collected through face-to-face survey administered using questionnaire during and after the event, yielding usable responses from 284 stallholders in Jakarta and Palembang venues and 19 official partners. The results show that the respondents hired additional workers during the event and they also generated additional sales, profit of which was partly used to scale up their businesses. However, future event can generate greater impact to local businesses with more effective socialization, simpler registration, and better stalls arrangements including more strategic location, better electricity and water supplies, and easier loading access to the venues.